2016
DOI: 10.1515/amm-2016-0187
|View full text |Cite
|
Sign up to set email alerts
|

Hot Processing of Cast and PM Ti-6Al-4V Alloy

Abstract: Quantitative and qualitative evaluation of the influence of the applied sample morphology as well as parameters of deformation on the microstructure and selected properties of Ti-6Al-4V alloy after deformation was presented. Both cast Ti-6Al-4V alloy and powder compacts were used as the material under investigation. P/M preform was produced from the mixture of elemental powders, by hot compaction. The samples of compacts as well as cast alloy were subjected to plastometric tests under various conditions. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The hot compression process was scheduled according to the scheme presented in figure 4a. The results of the discussed flow behavior of the examined alloys were previously reported by Wojtaszek andŚleboda (2013, 2014), Wojtaszek et al (2014, 2016), and Zyguła et al (2017. Tests were performed using different types of thermo-mechanical simulators, which were able to simulate various ranges of processing conditions.…”
Section: Flow Behaviorsupporting
confidence: 81%
See 1 more Smart Citation
“…The hot compression process was scheduled according to the scheme presented in figure 4a. The results of the discussed flow behavior of the examined alloys were previously reported by Wojtaszek andŚleboda (2013, 2014), Wojtaszek et al (2014, 2016), and Zyguła et al (2017. Tests were performed using different types of thermo-mechanical simulators, which were able to simulate various ranges of processing conditions.…”
Section: Flow Behaviorsupporting
confidence: 81%
“…For the numerical analysis of forging selected structural part out of the investigated alloys, commercial QForm 3D software was used. The results of the numerical modeling of the hot forging of PM titanium alloys as well as its verification in industrial conditions were previously reported by Wojtaszek andŚleboda (2013, 2014), Wojtaszek et al (2014Wojtaszek et al ( , 2016, Wojtaszek (2018). In order to properly design and -127 -COMPUTER METHODS IN…”
Section: Fem Simulations and Process Verification In Industrial Conditionsmentioning
confidence: 89%
“…When producing high-loaded details, one of the problems is the presence of surface tensile stresses (Gnyusov et al, 2017;Hou et al, 2018). They can substantially reduce the mechanical, resource, and fatigue characteristics of products (Wojtaszek et al, 2016;Sakhvadze et al, 2017;Pei & Duan, 2017;Huang et al, 2018). The residual stresses exist in products in the absence of external actions.…”
Section: Introductionmentioning
confidence: 99%